Peliminary exploration on the differential diagnosis between meningioma and schwannoma using contrast-enhanced T1WI flow-sensitive black-blood sequence - Cao, Xin; Lv, Kun; Xu, Siting; Feng, Zhe; Yin, Xuyang; Pan, Lei; Geng, Daoying; Zhang, Jun (Frontiers in Oncology, 2023)
Contrast-enhanced T1WI flow-sensitive black-blood (CE-T1WI FSBB) is a newly developed sequence which had not been widely used for differential diagnosis of brain tumors. To quantify the pre-operative imaging features of intratumoral microbleeds and intratumoral vessels using CE-T1WI FSBB scan and study the differences in biological behavior of meningiomas and schwannomas underlying the imaging features. Seventy-three cases of meningiomas and 24 cases of schwannomas confirmed by postoperative pathology were included. Two neuroradiologists independently counted intratumoral vessels and intratumoral microbleeds based on CE-T1WI FSBB images. The vessel density index (VDI) and microbleed density index (MDI) were the number of intratumoral vessels and the number of intratumoral microbleeds divided by the tumor volume, respectively. The consistency test of intratumoral vessel count and intratumoral microbleed count based on CE-T1WI FSBB were summarized using 2-way random intraclass correlation coefficients (ICC). Mann–Whitney U-test and chi-square test were used to determine significant differences between meningiomas and schwannomas, and fibrous meningiomas and epithelial meningiomas. P<0.05 was considered statistically significant. The ICC of intratumoral vessels count and intratumoral microbleeds count were 0.89 and 0.99, respectively. There were significant differences in the number of intratumoral microbleeds (P<0.01) and MDI values (P<0.01) between meningiomas and schwannomas. There were no differences in the number of intratumoral vessels (P=0.64), VDI (P=0.17), or tumor volume (P=0.33). There were also differences in the number of intratumoral microbleeds (P<0.01), the MDI value (P<0.01), and the sex of patients (P<0.05) between fibrous meningiomas and epithelial meningiomas. CE-T1WI FSBB can be a new technique for differentiating schwannomas from meningiomas, and even different types of meningiomas. Schwannomas have a higher incidence of intratumoral hemorrhage, more intratumoral microbleeds, and higher MDI values than meningiomas, which provides a new basis for preoperative differential diagnosis and treatment decisions.